(untitled) (Journal of Hama University, 2022)
Oral health is very important because the mouth is the main gateway for various germs to enter the human body. These germs are abundant in the oral cavity. When these germs are not removed, they form with food remains what is called bacterial plaque. This bacterial plaque leads to the development of various oral diseases. Therefore, many methods must be used to remove bacterial plaque, such as Chlorhexidine showed good results against oral bacteria. Determination of the effect of 0.12% chlorhexidine solution on Streptococcus Mutans in 9-12-year children.The research was selected (25 male children and 25 female children), after obtaining the consent of the children’s parents. The sample will be taken (in the morning, with children prohibited from brushing their teeth and from eating and drinking except for water). We ask the child to chew the paraffin wax for one minute until the piece of wax becomes soft and allows him to swallow the saliva and then chew it for another two minutes. Finally, the child is asked to keep a piece of wax in his mouth and spit the collected saliva into the sterile container used to transport the samples. Then we use 10 ml of mouthwash containing 0.12% chlorhexidine and ask the child to put it inside his mouth, warning him not to swallow it and move it for two minutes and then spit it out of the mouth. After one hour, we ask the child to repeat the process of chewing the paraffin wax and then take the second saliva sample by making him spit into the sterile container other than the sample of the first bottle. The saliva sample will be transferred to the Faculty of Veterinary Medicine at Hama University immediately. Then we do serial dilution of the sample and then we perform bacterial culture on the culture of Streptococcus Mutans previously prepared. Then the germs are transferred to the National Hama Hospital for the incubation process. After the end of the incubation time for each dish and the appearance of bacterial colonies, we start the process of bacterial colony counting .The rate of decrease in the number of colonies when using chlorhexidine rinses was 87.96, and the decrease in the number of bacteria (bacteria in CFU/ml) was 82.34%. Conclusion: The results of this study showed that chlorhexidine is effective in reducing Streptococcus Mutans